1983
DOI: 10.1364/ol.8.000024
|View full text |Cite
|
Sign up to set email alerts
|

Third-harmonic generation in a pulsed supersonic jet of xenon

Abstract: Third-harmonic generation to 1182 A is reported in a pulsed supersonic jet of xenon. Using a valve equipped with a 1-mm-diameter nozzle and for an incident power of 18 MW at 3547 A, I have obtained a peak power of 260 W in a 2.9-nsec pulse, corresponding to 4.7 x 10(11) photons per pulse and an average power of 7.5 microW at 1182 A. The measured conversion efficiency is comparable with that in a bulk-gas cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…Kung and coworkers have further demonstrated that mixing of gases can enhance the THG-conversion efficiency even more (Kung 1983). Mixing allows for the optimization of the nonlinear susceptibility with one gas (xenon), and the loss in the phase matching is compensated by adding argon gas, which has different dispersion properties at the wavelengths chosen.…”
Section: Phase Matching In the Tight-focus Limitmentioning
confidence: 99%
See 4 more Smart Citations
“…Kung and coworkers have further demonstrated that mixing of gases can enhance the THG-conversion efficiency even more (Kung 1983). Mixing allows for the optimization of the nonlinear susceptibility with one gas (xenon), and the loss in the phase matching is compensated by adding argon gas, which has different dispersion properties at the wavelengths chosen.…”
Section: Phase Matching In the Tight-focus Limitmentioning
confidence: 99%
“…Mixing allows for the optimization of the nonlinear susceptibility with one gas (xenon), and the loss in the phase matching is compensated by adding argon gas, which has different dispersion properties at the wavelengths chosen. The optimized mixing ratio depends on the choice of the b parameter and the cell length L. By this means, a conversion efficiency of 2.8% was experimentally demonstrated (Kung 1983 Figure 3 Optimization of phase matching in xenon gas by varying the gas pressure. Conditions b/L = 0.025 and f/L = 0.5, the focus positioned at the center of the cell.…”
Section: Phase Matching In the Tight-focus Limitmentioning
confidence: 99%
See 3 more Smart Citations